Respostas

2013-12-17T18:33:11-02:00
L) 2x+3x-9x=2-10
 -4x=-8
 x= -8/-4
x=2                         s={2}

m) x+2x-1-3=x
2x-x+x=1+3
2x=4
x=4/2                          
x=2              s={2}

n)-10+4-2x=-4x-7
-2x+4x=-7+10-4
2x=3-4
2x=-1
x=-1/2                    s={-1/2}

0) 2-4x=32-18x+12
-4x+18x=32+12-2
14x=44-2
14x=42
x=42/14
x=3          s={3}



1 1 1
2013-12-17T18:41:10-02:00
L)10 - 9x+ 2x = 2 - 3x
- 9x + 2x + 3x = 2 - 10
- 4x = - 8
x = - 8 ÷ (- 4)
x = 2

m) x + 2x - 1 - 3 = x
x + 2x - x = 1+ 3
2x = 4
x = 4 ÷ 2
x = 2

n) - 10 + 4 - 2x = - 4x - 7
- 2x + 4x = - 7 + 10 - 4
2x = - 1
x = - 1 ÷ 2
x = - 0,5

o) 2 - 4x = 32 -18x + 12
- 4x + 18x = 32 + 12 - 2
14x = 42
x = 42 
÷ 14
x = 3